Intelligent Learning Environments for 21st-Century Competencies: Connecting Engagement, Achievement, and Teamwork in Vocational Training - Chui, Len Wan; Heng, Cheng Jie; Yang, Wang Li (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2025)
This study investigates the integration of smart classrooms and collaborative learning to enhance 21st-century competencies in Taiwan’s vocational education. Using a mixed-methods approach, the research involved surveys with 300 students and qualitative data from classroom observations and teacher interviews in both urban and rural schools. Results showed significant improvements in student engagement, academic achievement, and soft skills such as teamwork (+27%), communication (+18%), and problem-solving (+25%). Smart classrooms also helped narrow the digital divide, yet challenges remain in rural areas, including limited teacher training (60%), inadequate internet access (35%), and infrastructure constraints (75%). Despite these issues, institutional readiness was relatively high—73% for training and 82% for infrastructure. The findings suggest that while smart classrooms positively impact learning outcomes, long-term success requires equitable access, sustained infrastructure support, and targeted professional development. Future research should explore their long-term effects on employability and the potential of adaptive learning technologies for personalized vocational training.